2014
DOI: 10.1111/iwj.12274
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of the infected recurrent sacrococcygeal pilonidal sinus

Abstract: The aim of the present retrospective single centre study was to define the changes in the microbiological flora of the recurring sacrococcygeal pilonidal sinus (PS). Microbiological findings of swab samples of abscess-forming PS from 2000 to 2010 were evaluated. Within this time span, 73 swab samples were taken from primary sacrococcygeal pilonidal sinus (pPS) and 23 swab samples of patients with recurring sacrococcygeal pilonidal sinus (rPS). Our results show a statistically significant shift of the bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
1
15
0
1
Order By: Relevance
“…It is a disease that usually affects young adults. It has been suggested that hairs penetrating into the skin cause fistula formation, which starts a foreign body reaction (including partial epithelisation of the skin), ending with chronic fistula or inflammation …”
Section: Introductionmentioning
confidence: 99%
“…It is a disease that usually affects young adults. It has been suggested that hairs penetrating into the skin cause fistula formation, which starts a foreign body reaction (including partial epithelisation of the skin), ending with chronic fistula or inflammation …”
Section: Introductionmentioning
confidence: 99%
“…Thus, either preoperative bacterial colonization in chronic PSD did not cause postoperative wound complications and recurrence or the antibiotic targeting of the bacteria responsible for impaired wound healing and recurrence was insufficiently targeted. A recent study of Ardelt et al [ 25 ] was able to demonstrate a significant shift in the microbial flora in recurring PSD towards the Gram-positive range as well as a tendency towards the aerobic range. Hitherto, these bacterial changes did not alter the recurrence rate or time to recurrence in repeated disease, as 4th recurrences tend to recur not much earlier than 2nd or 1st recurrences [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the visualisation of the fistulas with MB usage, its antimicrobial effect is beneficial. In large abscess forming SPSD in particular, microbes are identified in approximately 80% of some cases (22) Some several publications have discussed phenol injection into the fistulas (23,24). The inflammation within the fistula system causes scarring.…”
Section: Discussionmentioning
confidence: 99%